Legal regulation of China’s carbon emissions trading market - Yu, Min; Bai, Jia-Mei; Qiu, Yuqin; Lin, Yingjie; Liu, Shaojun (Frontiers in Environmental Science, 2025)
The legal regulation of China’s carbon emissions trading market is crucial in the country’s efforts to combat climate change and transition to a low-carbon economy. As the world’s largest emitter of greenhouse gases, China launched its national carbon market in 2021, building on years of regional pilot programs. This paper analyzes the legal framework governing China’s carbon trading system, examining key legislation, policy developments, and regulatory mechanisms. The paper highlights the central role of the Ministry of Ecology and Environment in overseeing the market, as well as the legal principles guiding carbon allowance allocation and compliance requirements for businesses. Additionally, it addresses challenges such as the need for enhanced market transparency, stronger enforcement of non-compliance penalties, and the integration of China’s carbon market with international trading platforms. While China’s carbon trading market has made notable progress, the paper argues that further legal reforms are needed to improve its effectiveness in achieving carbon neutrality goals. It concludes with recommendations to strengthen the legal and regulatory framework, enhancing the market’s efficiency, transparency, and global integration.